Analisis Risiko Ketidaktercapaianya Standar ( ET:BT ) Berthing Time Pelayanan Kapal Dengan Metode Fuzzy dan Bowtie Analysis di PT. Pelindo III Cabang Gresik - Diah Fitri Rahmatianti; Roziana Ainul Hidayati; Abdurrahman Faris Indriya Himawan (Jurnal Mahasiswa Manajemen, 2022)
Background - PT Pelindo III is located at PT Pelindo Tanjung Perak Surabaya. Ship visits in the last three years have increased. Based on a report published on the official website of PT Pelindo III, namely an increase from 2015–2017 was 77,104,361 Gross Tonage in 2015, then 92,622,356 Gross Tonage in 2016, and 94,346,201 Gross Tonage in 2017. Objective - This study aims to determine the causes and impacts of risks that may occur due to non-achievement of performance standards (ET:BT) Berthing Time for ship services at PT Pelindo III Gresik Branch and identify the biggest risks. Design/Methodology/Approach - This research is a qualitative research using primary data and secondary data. Data collection techniques in this study are through observation, interviews and documentation. Findings - The results of this study indicate that there are four risks, namely: Dwelling Time, Idle Time and High Notes, Ship Queuing, and Trucking. The biggest risk is in Dwelling Time with a probability value of 0.96 which means that the level of risk posed is very risky. Research implications - This research contributes to employees who work at PT Pelindo III Gresik Branch who knows operational conditions both in the field and outside the field. Research limitations - This research was only conducted on the operational system of PT Pelindo III Gresik Branch